2020
DOI: 10.1371/journal.pone.0232632
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous detection of Mycobacterium tuberculosis complex and resistance to Rifampicin and Isoniazid by MDR/MTB ELITe MGB® Kit for the diagnosis of tuberculosis

Abstract: The MDR/MTB ELITe MGB ® Kit on the ELITe InGenius ® platform (ELITechGroup SpA, Italy) is the first system for simultaneous detection of the Mycobacterium tuberculosis complex (MTBc) genome and the main mutations responsible for resistance to Isoniazid (inhA, katG) and Rifampicin (rpoB), from decontaminated and heat inactivated samples. In this study we compared the performance of the MDR/MTB ELITe MGB ® Kit (ELITe) with culture in 100 pulmonary and 160 extra-pulmonary samples. The sensitivity and specificity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
2
3
2
Order By: Relevance
“…The sensitivity of the MTB/MDR ELITe MGB ® Kit on the extra-pulmonary samples observed in this study was moderate, and lower than the sensitivity reported by Bisognin et al (86.3%; CI95 (76.7; 92.9)) [10]. Using the Xpert MTB/RIF Ultra, a recent meta-analysis found a much higher sensitivity (85.6%; CI95 (76.7; 91.5)) on extra-pulmonary samples [12], suggesting that the latter test could be more sensitive on this type of sample than the MTB/MDR ELITe MGB ® Kit.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…The sensitivity of the MTB/MDR ELITe MGB ® Kit on the extra-pulmonary samples observed in this study was moderate, and lower than the sensitivity reported by Bisognin et al (86.3%; CI95 (76.7; 92.9)) [10]. Using the Xpert MTB/RIF Ultra, a recent meta-analysis found a much higher sensitivity (85.6%; CI95 (76.7; 91.5)) on extra-pulmonary samples [12], suggesting that the latter test could be more sensitive on this type of sample than the MTB/MDR ELITe MGB ® Kit.…”
Section: Discussioncontrasting
confidence: 87%
“…The overall sensitivity and specificity of the MTB/MDR ELITe MGB ® Kit reported in this study were very good, and the ROC curve analysis indicated a high accuracy of the test for TB diagnosis. Nevertheless, the overall sensitivity and the sensitivity on pulmonary samples were slightly inferior compared to these reported by Bisognin et al (90.8%; CI95 (84.6; 94.6) and 98.0%; CI95 (89.3; 99.9), respectively) [10]. This discrepancy is probably due to the way the samples were selected, as the MTB inoculum was higher in the latter study: a majority of the pulmonary samples were smear-positive (44/50), and when MTB was detected, the Ct of IS6110 was ≤31 (molecular typing feasible) for 95.5% of the pulmonary samples and 46.2% of the extra-pulmonary samples.…”
Section: Discussioncontrasting
confidence: 68%
“…Interestingly, the ELITe assay seems sensitive enough to detect pauci-bacillary TB. Sensitivity was comparable to that published by Bisognin et al [9], and higher than that observed by Hodille et al, in routine clinical context in our study. Considering the ELITe negatives, 15 were smear-positive, among which 13 were due to the non-tuberculosis mycobacteria M. intracellulare (n = 3), M. avium (n = 5), M. fortuitum (n = 1), M. chimaera (n = 2), M. abscessus susp.…”
Section: Discussionsupporting
confidence: 91%
“…Considering the ELITe negatives, 15 were smear-positive, among which 13 were due to the non-tuberculosis mycobacteria M. intracellulare (n = 3), M. avium (n = 5), M. fortuitum (n = 1), M. chimaera (n = 2), M. abscessus susp. bolletii (n = 1), and M. genavense (n = 1), and 2 were false-positive microscopic examinations likely due to Corynebacterium spp., indicating very high specificity of ELITe assay, which was also observed by Bisognin et al (99.23%) and Hodille et al (100%) [9,10]. Among the nine discordant results, four were false-negative ELITe results obtained from four culturediagnosed TB with negative microscopic examinations owing to their low bacillary load in the specimens.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation